An Assessment of the economic and social impacts of climate change on the water sector in the Caribbean : the central role of water - Llanes-Regueiro, Juan (UN New YorkUS, 2013)
Contains background analysis of links between the hydrological cycle and climate change, and the central role of water. Analyses the climate and hydrological cycle in the Caribbean, including the hydro-meteorological characteristics and impacts on water resources, that gives a picture of future precipitation patterns for the Caribbean and a country perspective, assessing the resource base in the past and towards 2050 and 2100. Analyses the possible impacts on groundwater due to sea level rise and several aspects related to water management.